Toxicity of chromated copper arsenate: a study in mice - Matos, Rita Cerejeira (2013)
Chromated copper arsenate (CCA) was widespread used as a chemical wood preservative with application in the construction of playground equipment, fences, jetties, and naval. Environmental protection agency (EPA) had limited the use of CCA-treated wood on 2002, due to probable implications on both human and environmental health. Although this fact, several industries pursue the use of this product within their manufactories. In addition, the durability of this wood for 60 years, makes these treated products an hazard to the public health. In the present work, studies were explored exposing mice to CCA, during 14, 24, 48, and 96 h for the assessment of acute toxicity of CCA. Kidney and liver were removed, prepared for histology and for metalloid, and copper content evaluation by high resolution inductively coupled plasma mass spectroscopy. The histological results evidenced apparently normal structures for control animals and group exposed to As2O5. On the contrary, the renal sections of the animals treated with CCA revealed epithelium cells desquamation, hyaline, and granular casts in renal tubules lumen. Furthermore, high levels of arsenic were detected in the kidney of animals treated with CCA over 14 and 48 h, being significantly greater than controls. Although this approach underlines the potential hazard of CCA on some vital organs, further testing may be required to establish the impacts on other functions.